Gratitude in Hajat Bumi - Dewi, Sinta Maria; Maftuh, Bunyamin (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This article aims to examine the value of gratitude in Hajat Bumi. The scope of the discussion of this paper are the origin and understanding of Hajat Bumi, the conditions for implementing it, and the process of implementing it and the value of gratitude contained in it and how is it applied at elementary school. Hajat Bumi is a ritual carried out by villagers as an expression of gratitude for the abundance of earth harvests for one year. The method used in this study is literature study, interview and observation. Based on the results of the research the main values contained in the Hajat Bumi are the values of gratitude. The usefulness of the results of this paper is to provide an understanding of the value of gratitude contained in the activities of Hajat Bumi and is expected to provide religious provisions to children who live in modern times as a foundation in carrying out life in the future